The wicked witchweed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Striga or witchweed (Striga hermonthica) is well on its way to joining the list of the world s worst weeds, and is already top of list of many an African farmer. It is a parasitic weed that penetrates the roots of other plants, diverting nutrients...